Pemberian Rootone F dan Asal Bagian Stek Terhadap Pertumbuhan Akar Stek Daun Lidah Mertua (Sansevieria trifasciata lorentii) - Brigita Gracia Falentiani Namupraing; I Nengah Suaria; Made Suarta (GEMA AGRO, 2019)
These research aims to find out the influence of the Rotoone F interactions and the cuttage part of lidah mertua leaf. It was conducted at the Faculty of Agriculture Green House in Warmadewa University, was commencing on 18th April 2017 until 18th July 2017. This kind of experiment was a factorial one that using Design of Experiment (RAL). First treatment was Rootone F that 4 levels consistend which 0 g/stek as control (R0); 0,2 g/stek (R1); 0,4 g/stek (R2); 0,6 g/stek (R3). Second treatment was the cuttage part of the leafthat 3 levels consisted wich the tip (SU), the middle (ST), petiole (SP). The result has been shown that the best root growth can be obtained without Rootone F and part of the tip leaf